Quantitative PCR as a marker for preemptive therapy and its role in therapeutic control in Trypanosoma cruzi/HIV coinfection. - Vera Lúcia Teixeira de Freitas; Christina Terra Gallafrio Novaes; Ana Marli Christovam Sartori; Noemia Barbosa Carvalho; Sheila Cristina Vicente da Silva; Érika Shimoda Nakanishi; Fernando Salvador; Cleudson Nery de Castro; Rita Cristina Bezerra; Elizabeth Visone Nunes Westphalen; Caroline Medeji Ramos de Oliveira; Felipe Delatorre Busser; et al. (Public Library of Science (PLoS), 2024)
Background Trypanosoma cruzi and HIV coinfection can evolve with depression of cellular immunity and increased parasitemia. We applied quantitative PCR (qPCR) as a marker for preemptive antiparasitic treatment to avoid fatal Chagas disease reactivation and analyzed the outcome of treated cases. Methodology This mixed cross-sectional and longitudinal study included 171 Chagas disease patients, 60 coinfected with HIV. Of these 60 patients, ten showed Chagas disease reactivation, confirmed by parasites identified in the blood, cerebrospinal fluid, or tissues, 12 exhibited high parasitemia without reactivation, and 38 had low parasitemia and no reactivation. Results We showed, for the first time, the success of the timely introduction of benznidazole in the non-reactivated group with high levels of parasitemia detected by qPCR and the absence of parasites in reactivated cases with at least 58 days of benznidazole. All HIV+ patients with or without reactivation had a 4.0-5.1 higher chance of having parasitemia than HIV seronegative cases. A positive correlation was found between parasites and viral loads. Remarkably, treated T. cruzi/HIV-coinfected patients had 77.3% conversion from positive to negative parasitemia compared to 19.1% of untreated patients. Additionally, untreated patients showed ~13.6 times higher Odds Ratio of having positive parasitemia in the follow-up period compared with treated patients. Treated and untreated patients showed no differences regarding the evolution of Chagas disease. The main factors associated with all-cause mortality were higher parasitemia, lower CD4 counts/μL, higher viral load, and absence of antiretroviral therapy. Conclusion We recommend qPCR prospective monitoring of T. cruzi parasitemia in HIV+ coinfected patients and point out the value of pre-emptive therapy for those with high parasitemia. In parallel, early antiretroviral therapy introduction is advisable, aiming at viral load control, immune response restoration, and increasing survival. We also suggest an early antiparasitic treatment for all coinfected patients, followed by effectiveness analysis alongside antiretroviral therapy.